2003
DOI: 10.1152/ajpcell.00269.2003
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein ameliorates death receptor-mediated apoptosis in lung cancer cells

Abstract: Parathyroid hormone-related protein (PTHrP) is expressed in more advanced, aggressive tumors and may play an active role in cancer progression. This study investigated the effects of PTHrP on apoptosis after UV irradiation, Fas ligation, or staurosporine treatment in BEN human squamous lung carcinoma cells. Cells at 70% confluency were treated for 24 h with 100 nM PTHrP-(1-34), PTHrP-(38-64), PTHrP-(67-86), PTHrP-(107-139), or PTHrP-(140-173) in media with serum, exposed for 30 min to UV-B radiation (0.9 mJ/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The antiapoptotic properties of PTHrP have been observed in a variety of cell types (20,(31)(32)(33)(34)(35)(36)(37). While the molecular mechanisms by which PTHrP signaling in the osteoblast prevents apoptotic cell death remain to be determined, a number of them may be operative.…”
Section: Discussionmentioning
confidence: 99%
“…The antiapoptotic properties of PTHrP have been observed in a variety of cell types (20,(31)(32)(33)(34)(35)(36)(37). While the molecular mechanisms by which PTHrP signaling in the osteoblast prevents apoptotic cell death remain to be determined, a number of them may be operative.…”
Section: Discussionmentioning
confidence: 99%
“…PTHrP demonstrates widespread distribution in lung carcinomas, being present in a high percentage of lung tumors (13) of all histological types (4). In addition, PTHrP is an autocrine growth factor for lung cancer cells (5) and protects them from apoptosis (11), characteristics that could contribute to a cancer's capacity for unregulated growth. Furthermore, PTHrP induces expression of metalloproteinases in carcinoma cells and may stimulate angiogenesis in tumors (3,17) These factors are important in providing a carcinoma with the means to develop its blood supply, to invade into adjacent tissues, and to metastasize.…”
mentioning
confidence: 99%
“…A recent study (11) reported that the PTHrP-derived peptide PTHrP-(140 -173) exerts regulatory effects on lung cancer cell apoptosis. Pretreatment with 100 nM PTHrP-(140 -173) for 24 h protected BEN human squamous lung carcinoma cells from the apoptotic effects of ultraviolet (UV)-B irradiation or activating Fas antibody (11).…”
mentioning
confidence: 99%
“…Cells were plated at 5,000 cells/well in 96-well plates in growth media for proper cell adherence. 8 The following day, cells were incubated in serum free media with 1 mg/ml BSA overnight for synchronization of cell growth cycle. The experiment was initiated by transferring cells to growth media with appropriate treatments.…”
Section: Methodsmentioning
confidence: 99%
“…PTHrP increases the likelihood of bone metastases in mice injected with small cell lung carcinoma cells 7 and it protects squamous lung carcinoma cells from apoptosis. 8 Since PTHrP is expressed in two-thirds or more of non-small cell lung carcinomas in humans, 9 it could be a reasonable target for a lung cancer therapy.…”
Section: Combinatorial Library Discovery Of Small Molecule Inhibitorsmentioning
confidence: 99%